Influencia de la gestión pública en el fomento del emprendimiento en el cantón San Jacinto de Buena Fe, periodo 2022 – 2023 - Avilés Araujo , Francisco Emilio (2023)
During the year 2023, research has been carried out focused on the impact of public management on stimulating entrepreneurship in the canton of San Jacinto de Buena Fe, located in the province of Los Ríos. The primary objective of this study has been to thoroughly evaluate the influence of public policies in promoting entrepreneurship in said canton. The methodology used covers a field investigation that included a census of 70 entrepreneurs from the canton, regular participants in the entrepreneurship fairs organized by the GAD. In addition, a bibliographic review was carried out on topics related to entrepreneurship and public management. Among the main findings, the negative perception that entrepreneurs have about the current economy of the canton stands out for the development of their businesses. Also evident is the scarcity of public policies that support the entrepreneurial sector, the lack of communication about regulations that directly affect them and the limited willingness of financial institutions to support the creation of new ventures, due to the difficulties in requesting financing and the high interest rates. The results obtained offer a complete vision of the current situation of the entrepreneurship, they also provide valuable information to actively promote this activity, it is positioned as an essential resource for local development, it also serves as a model for other cantons in the province to follow, the successful practices identified, promoting public policies favorable to entrepreneurs